2021
DOI: 10.3390/ijms222413189
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Rare Mutations of SCN9A, DPP4, ABCA13, and SYT14 in Schizophrenia and Bipolar Disorder

Abstract: Rare mutations associated with schizophrenia (SZ) and bipolar disorder (BD) usually have high clinical penetrance; however, they are highly heterogeneous and personalized. Identifying rare mutations is instrumental in making the molecular diagnosis, understanding the pathogenesis, and providing genetic counseling for the affected individuals and families. We conducted whole-genome sequencing analysis in two multiplex families with the dominant inheritance of SZ and BD. We detected a G327E mutation of SCN9A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…These symptoms and diagnoses were ADHD, anxiety disorder, ID, delay in speech, and febrile convulsion (Table 1). Our results in the same line with the previous studies showing the association between variants in the ABCA13 gene and different psychiatric disorders such as bipolar disorder, schizophrenia, major depressive disorder, ADHD, and ASD [Yoshida et al, 2016;Chen et al, 2021aChen et al, , 2021bLiu et al, 2021;Nakato et al, 2021]. Martin et al investigated the pathways in the etiopathogenesis of ADHD and ASD using CNV analysis and found a deletion involving the ABCA13 gene in a patient with ASD [Martin et al, 2014].…”
Section: Relationship Between Autism Spectrumsupporting
confidence: 92%
See 1 more Smart Citation
“…These symptoms and diagnoses were ADHD, anxiety disorder, ID, delay in speech, and febrile convulsion (Table 1). Our results in the same line with the previous studies showing the association between variants in the ABCA13 gene and different psychiatric disorders such as bipolar disorder, schizophrenia, major depressive disorder, ADHD, and ASD [Yoshida et al, 2016;Chen et al, 2021aChen et al, , 2021bLiu et al, 2021;Nakato et al, 2021]. Martin et al investigated the pathways in the etiopathogenesis of ADHD and ASD using CNV analysis and found a deletion involving the ABCA13 gene in a patient with ASD [Martin et al, 2014].…”
Section: Relationship Between Autism Spectrumsupporting
confidence: 92%
“…There are large scale sequencing studies as well as genome-wide association studies of schizophrenia, bipolar disorder, and ASD-detecting effects of the ABCA13 gene interacting partners on NDDs [Satterstrom et al, 2020]. These accumulating data support the involvement of the ABCA13 gene and interacting partner genes in etiopathogenesis of the NDDs [Chen et al, 2021a[Chen et al, , 2021bLiu et al, 2023]. The aim of this study was to elucidate the role of ABCA13 gene single-nucleotide variants (SNVs) in the etiopathogenesis of autism by investigating the impact of ABCA13 gene variants under psychiatric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a large part of neuropsychiatric patients’ genetic landscape is still missing. Several studies have indicated that oligemic involvement is part of the genetic landscape of neurodevelopmental disorders [ 32 , 88 , 89 , 90 , 91 ]. Notably, in a recent study, John and colleagues reported the detection of five rare heterozygous variants in a schizophrenia multiplex family.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested using NGS as a first-tier genetic test for neurodevelopmental disorders [ 29 , 30 ]. Our group also identified several rare genetic mutations associated with ID and psychiatric conditions using NGS [ 31 , 32 , 33 ]. Our studies support that NGS helps establish a personalized molecular diagnosis for neurodevelopmental and psychiatric disorders [ 34 ].…”
Section: Introductionmentioning
confidence: 99%